Measurement and Analysis of Human Infant Crawling for Rehabilitation: A Narrative Review - Xiong, Qi L.; Wu, Xiao Y.; Liu, Yuan; Zhang, Cong X.; Hou, Wen S. (Frontiers in Neurology, 2021)
When a kid shows signs of potential motor developmental disorders, early diagnosis of central neural system (CNS) impairment is beneficial. Known as the first CNS controlled mobility for most of infants, mobility during crawling usually been used in clinical assessments to identify motor development disorders. The current clinical scale of motor development during crawling stage are relatively subjective. Objective and quantitative measures of infant crawling afford the possibilities to identify those infants who might benefit from early intervention as well as the evaluation of intervention progress. Thus, increasing researchers have explored objective measurements of infant crawling in typical and atypical developing infants. However, there’s a lack of comprehensive review on infant crawling measurement and analysis toward bridging the gap between research crawling analysis and potential clinical applications. In this narrative review, we provide a practical overview of the most relevant measurements in human infant crawling, including acquisition techniques, data processing methods, features extraction, and the potential value in objective assessment of motor function in infancy, meanwhile, the possibilities to develop crawling training as early intervention to promote the locomotor function for infants with locomotor delays are also discussed.